Pengaruh Motivasi Kerja, Komitmen Dan Kepuasan Kerja Terhadap Kinerja Karyawan CV DIGINUSA TUFFERO - Saroh, Pristi Maimuna; Djaelani, Abdul Kodir; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to analyze the influence of work motivation, commitment, and job satisfaction variables on employee performance at CV Diginusa Tuffero. The method used in this study is a quantitative purposive sampling method using a saturated sampling technique, where the sampling method involves all members of the population as research samples. The population in this study consists of all employees working at CV Diginusa Tuffero, with a sample size of 37 respondents selected using non-probability sampling techniques. The data collected are primary data obtained through the distribution of online questionnaires using Google Forms to employees. The research results indicate that Work motivation has a positive significant influence on employee performance. Work commitment also has a positive significant influence on employee performance. Job satisfaction has a positive significant influence on employee performance. the variables of work motivation, commitment, and job satisfaction have a positif significant influence on employee performance Keywords: Work Motivation, Commitment, Job Satisfaction and Employee Performance